The Perspective of Teachers towards Soft skills in English Language Teaching and Learning at Souphanouvong University - BANDASACK, Bouaphanh; KEOBOUALAPHETH, Soulideth; HUNGSAVATH, Thongkham (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
In this research project, the researcher aimed to investigate the teachers' perspective on soft skills in English language teaching and learning at the Faculty of Languages, Souphanouvong University. A quantitative method was employed to achieve the objective. The instrument used for this study was a questionnaire on four skills: communication skills, collaboration skills, creative thinking skills, and critical thinking/problem-solving skills, using a 5-point Likert scale. The questionnaires included 43 items in total. They were distributed to the population of English language teachers in the faculty, a total of 27 participants, with 13 females and 14 males. The data was analyzed using the SPSS (version 26) program to calculate frequency, percentage, mean value, and standard deviation. The results showed that from the teachers' perspective, communication skills were the most important with Mean = 4.50 and S.D = 0.39. This was followed by creative thinking skills with Mean = 4.27 and S.D = 0.43, collaboration skills with Mean = 4.22 and S.D = 0.45, and critical thinking/problem-solving skills with Mean = 4.21 and S.D = 0.53. These three were all close in terms of mean, and although still important, slightly less so than communication skills. Based on these results, teachers' attitudes toward soft skills in English language teaching and learning are crucial and useful to integrate into the classroom.